Implementation of Sustainable Development Goals (SDGS) in Indonesia From an Islamic Economic Perspective - Farida, Lusiana; Nuzula, Vira Virdausi (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2024)
Indonesia is committed to the success of the Sustainable Development Goals (SDGs) as part of the sustainable economic development efforts that are also part of global commitments. This paper aims to analyze the extent of the government's success in implementing the SDGs program, focusing on goals related to welfare. In addition, the author will also explore the relevance of implementing the SDGs in Indonesia from an Islamic economic perspective. The research method used is Systematic Literature Review, which is a systematic and structured approach to assess, analyze, and synthesize the literature relevant to the research topic. The results of the study show that the regulatory aspects of SDGs in Indonesia have shown significant progress and relevance to the principles of Islamic economics. However, in practice, there are various shortcomings and mismatches between welfare issues and the goals of the SDGs, especially from an Islamic economic perspective. This has contributed to the increase in social inequality in Indonesia in the last ten years. These findings-+-----------------------------------------------------------------